2017
DOI: 10.3389/fmicb.2017.00892
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Potential Influences Phenazine Production, Electron Transfer and Consequently Electric Current Generation by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa has gained interest as a redox mediator (phenazines) producer in bioelectrochemical systems. Several biotic and abiotic factors influence the production of phenazines in synergy with the central virulence factors production regulation. It is, however, not clear how the electrochemical environment may influence the production and usage of phenazines by P. aeruginosa. We here determined the influence of the electrochemical potential on phenazine production and phenazine electron transfer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 30 publications
2
35
2
Order By: Relevance
“…An additional argument to understand the dependence of PcPCL1606 of the oxygen, is the inability to produce phenazines and therefore the absence of it. Glasser et al (2014) reported that phenazine enable the proton-motive force by stimulate redox homeostasis and ATP synthesis, maintaining the bacterium survival in anaerobic environmental ( Glasser et al, 2014 ; Bosire and Rosenbaum, 2017 ; Askitosari et al, 2019 ). The non-production of phenazine by PcPCL1606 prevents it from having this resource to survive in oxygen-limiting conditions, and makes it a perfect candidate for the study of aer genes without the interference of these redox compounds ( Hernandez et al, 2004 ; Wang and Newman, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…An additional argument to understand the dependence of PcPCL1606 of the oxygen, is the inability to produce phenazines and therefore the absence of it. Glasser et al (2014) reported that phenazine enable the proton-motive force by stimulate redox homeostasis and ATP synthesis, maintaining the bacterium survival in anaerobic environmental ( Glasser et al, 2014 ; Bosire and Rosenbaum, 2017 ; Askitosari et al, 2019 ). The non-production of phenazine by PcPCL1606 prevents it from having this resource to survive in oxygen-limiting conditions, and makes it a perfect candidate for the study of aer genes without the interference of these redox compounds ( Hernandez et al, 2004 ; Wang and Newman, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenazine-1-carboxylic acid (PCA) is a type of redox-active phenazine and is produced by species of Pseudomonas and Actinomycetes. PCA possesses a relatively low for redox potential (E = −0.24 V vs. Ag/AgClsat) and is primarily involved in reversible redox cycling under oxygen-limited conditions (Bosire et al, 2016;Bosire and Rosenbaum, 2017). Reportedly, PCA rather than pyocyanin may be responsible for electron transfer from the cathode to Pseudomonas aeruginosa PA14 (Bosire and Rosenbaum, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PCA possesses a relatively low for redox potential (E = −0.24 V vs. Ag/AgClsat) and is primarily involved in reversible redox cycling under oxygen-limited conditions (Bosire et al, 2016;Bosire and Rosenbaum, 2017). Reportedly, PCA rather than pyocyanin may be responsible for electron transfer from the cathode to Pseudomonas aeruginosa PA14 (Bosire and Rosenbaum, 2017). In our previous our work, we established that PCA could perform the role of electron transfer and effectively improve current generation in microbial fuel cell by introducing the PCA pathway of P. aeruginosa in E. coli (Feng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A BPV device contains photosynthetic microorganisms that absorb and convert solar energy into chemical energy with minimal carbon footprint. 7,11,12 Despite the various electron shuttling pathways available, Bombelli et al 3 explained that algal BPV devices without redox mediators were simpler, more efficient, and cheaper in upscaled applications. [3][4][5][6][7] Instead of releasing carbon dioxide (CO 2 ), microalgae remove CO 2 from the surroundings for biomass production.…”
Section: Introductionmentioning
confidence: 99%
“…Electrons from the cells are ferried to the electrode through one of the following pathways: (a) direct electron transfer (DET), (b) an endogenous electron transfer mediator such as Flavin, or (c) an exogenous electron transfer mediator such as polypyrrole and polyaniline. 7,11,12 Despite the various electron shuttling pathways available, Bombelli et al 3 explained that algal BPV devices without redox mediators were simpler, more efficient, and cheaper in upscaled applications. In the recent years, DET from biofilms has been linked to enhanced electron transfer as direct contact with the anode minimizes internal potential loss.…”
Section: Introductionmentioning
confidence: 99%